DAKWAH KULTURAL PENDIDIKAN ISLAM MELALUI SAFARI RAMADHAN IKATAN GURU BUSTANUL ATHFAL STUDI MULTI SITUS DI BUNGKAL PONOROGO - Rohani, Imam; Muttaqin, Nurul (Journal of Islamic Science Community, 2024)
This research aims to describe community service activities in the form of cultural da'wah in order to fill the month of Ramadan. This research uses a qualitative approach with a multi-case and multi-site study type of research. The results of this research are that the cultural da'wah of Islamic education through the Ramadhan safari of the Bustanul Athfal teacher association, a multi-site study in Bungkal Ponorogo, was carried out in four different institutions with different themes. The sequence of activities is sequential, First, a missionary safari at Bustanul Athfal Aisyiyah Bancar with the theme of achieving victory in the month of Ramadhan. Second, a missionary safari in Bustanul Athfal Aisyiyah Bungkal (Dungulan) with the theme of being a pious wife/mother safe in the afterlife. Third, a missionary safari at Bustanul Athfal Aisyiyah Assalam Bancar with the theme of training children to fast from an early age. Fourth, a missionary safari at SD Muhammadiyah Bungkal with the theme of yaumiyah worship education. this activity.